Views of First-Time Expectant Mothers on Breastfeeding: A Study in Three Health Facilities in Accra, Ghana - Freda Intiful; Claudia Osei; Rebecca Steele-Dadzie; Ruth Nyarko; Matilda Asante (Advances in Public Health)
The objective of this study was to evaluate the views of first-time expectant mothers on breastfeeding. A qualitative study approach using focus group discussions was used to solicit the views of 25 expectant first-time mothers. The results indicated the intention to breastfeed, though some were willing to opt for formula feeding when the need arises. Knowledge on breastfeeding issues was minimal among this group. Common sources of information on breastfeeding issues were obtained from home (relatives), hospital, and television. The need to support and provide adequate education on breastfeeding issues is critical among this category of women.